2018
DOI: 10.1002/slct.201802065
|View full text |Cite
|
Sign up to set email alerts
|

SNS versus SNN Pincer Ligands: Electrochemical Studies and Their Palladium(II) Complexes as Electro‐Catalyst for Proton Reduction

Abstract: Electrochemical measurements on pincer ligands bis‐N‐(2,5‐dimethoxyphenyl)pyridine‐2,6‐dicarbothioamide (pdcta) and 6‐(4,7‐dimethoxy‐2‐benzothiazolyl)‐N‐(2,5‐dimethoxyphenyl)‐2‐pyridinecarbothioamide (pbcta) in N,N‐dimethylformamide (DMF) and dimethylsulfoxide (DMSO) on a glassy carbon working electrode revealed sulfur centred electrochemical processes. Spectroscopic, elemental and electrochemical analyses indicated that pdcta coordinated to Pd(II) via a κ3‐SNS mode to give 1 whereas pbcta coordinated via a κ3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Nevertheless, the shift in the C=N reduction potential was a key diagnostic tool in assessing the coordination of M 2+ to the hydrazone. Unlike the hydrazones, species 2 , 3 , 5 and 6 were more resistant to bond cleavage upon reduction, however the thienyl radicals generated from electrochemical processes may undergo chemical reactions which ultimately impede the reversibility of the process [7a–c] . Similar to the hydrazones, the coordination to M 2+ and resulting shift in the reduction potential of the thioamide is a diagnostic tool in assessing the coordination of 2 , 5 and 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the shift in the C=N reduction potential was a key diagnostic tool in assessing the coordination of M 2+ to the hydrazone. Unlike the hydrazones, species 2 , 3 , 5 and 6 were more resistant to bond cleavage upon reduction, however the thienyl radicals generated from electrochemical processes may undergo chemical reactions which ultimately impede the reversibility of the process [7a–c] . Similar to the hydrazones, the coordination to M 2+ and resulting shift in the reduction potential of the thioamide is a diagnostic tool in assessing the coordination of 2 , 5 and 6 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the improved electrochemical stability, the redox non‐innocence of these pyridyl based pincers may improve the stability of metal centers in various oxidation states in catalytic transformations. In these studies, [7b,c] it was found that the coordinating atoms of the ligand system influenced the electrocatalytic behavior in the hydrogen evolution reaction (HER). To further understand and develop these ligand systems, quantifying binding (formation) constants, and the relative equilibrium constants amongst these pyridyl thiazoles and thioamides ligand systems can also provide insights about the modifications that can be made to the ligand framework.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Pt(II) and Pd(II) complexes composed of NNS tridentate pincer ligands were found to have significant biological activities. [13][14][15][16][17][18][19] Both metals have similar chemistry but the later has less side effects and better solubility, which led researchers to focus on Pd(II) complexes as antitumor drugs. [13][14][15][16][17][18][19] Palladium complexes [Pd II (HY)Cl] built from H 2 Y(SNN) pincer ligands were previously prepared in our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Both metals have similar chemistry but the later has less side effects and better solubility, which led researchers to focus on Pd(II) complexes as antitumor drugs. [13][14][15][16][17][18][19] Palladium complexes [Pd II (HY)Cl] built from H 2 Y(SNN) pincer ligands were previously prepared in our laboratory. 20 The ligand H 2 Y (Scheme 1, left) was bound in anionic form to Pd(II) to form neutral cis and trans isomers.…”
Section: Introductionmentioning
confidence: 99%